Pemberdayaan Masyarakat Desa Talabiu Melalui Penyelenggaraan T-Fest ( Talabiu Festival) sebagai Upaya Pelestarian Adat dan Penguatan Ekonomi Lokal - Sahrul Akbar; Chaerul Anam; Muhammad Rimawan; Muhammad Badar (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service activities through the Community Service Program (KKN) are a form of implementation of the Tri Dharma of Higher Education (Tri Dharma) in community empowerment. This study aims to describe and analyze the empowerment process of the Talabiu Village community through the organization of T-Fest (Talabiu Festival) by STIE Bima students, as an effort to preserve local customs and strengthen the local economy. This activity was motivated by low community participation in preserving regional culture and the lack of economic innovation based on local potential The study used a descriptive qualitative approach with participatory methods, in which students played a direct role in designing and implementing the festival activities with the community. Data were collected through in-depth interviews with village officials, traditional leaders, and MSMEs, as well as observations of activities during the festival. The results indicate that the T-Fest successfully raised community awareness of the importance of preserving Talabiu customs and culture. The festival featured a variety of traditional arts, a local product exhibition, a culinary bazaar, and social activities involving all villagers. From an economic perspective, T-Fest opened up opportunities for MSMEs to introduce their products, increase sales, and expand their marketing networks. Furthermore, this activity fosters a sense of pride and solidarity among residents through collaboration between students and the community. In conclusion, T-Fest is a concrete example of community empowerment based on campus-village collaboration, where preserving traditional customs and improving the local economy can go hand in hand. This activity demonstrates the strategic role of KKN students in building cultural awareness and promoting economic independence in village communities.